Analysis of Burnout Levels of Judo Coaches in the COVID-19 Period: Mixed Method - Özgür Aktaş; Berna Karakoç; Önder Karakoç (Journal of Educational Issues, 2024)
This study was carried out to find out the burnout levels of judo coaches in COVID-19 period and to show how they will approach their profession and athletes in the period after the pandemic. 136 judo coaches from different coaching levels participated in the study. Maslach Burnout Inventory was used in the study. In addition, 3 qualitative questions were prepared by the researchers to find out the emotions of coaches during and after the pandemic and how they approached their athletes. IBM SPSS 22 statistical program was used to analyze the data in the study. Since the data were not normally distributed, non-parametric Mann Whitney U was used in paired group comparisons, while Kruskal Wallis H test was used for the comparison of more than two groups and significance level was taken as p < .05. Content analysis method was used to analyze the 3 qualitative questions. As a result, burnout levels of the judo coaches in the study were found to be low. No significant difference was found between the variables of gender, age and coaching level and burnout level. In addition, while coaches stated that they missed their profession and were waiting excitedly for trainings to start, more than half of them stated that their approaches to athletes will change after the pandemic.